The 2017 Declaration of Independence of Catalonia in French Documentary Cinema: Strategies Employed by the Public Audiovisual System to Minimise its Impact in France - Céspedes Gallego, Jaime (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2026)
This article focuses on two documentaries produced by French public television following the declaration of independence of Catalonia by the President of the Generalitat, Carles Puigdemont, on 10 October 2017: Catalogne, la bataille des mots and Catalogne, l’Espagne au bord de la crise de nerfs. We adopt a comparative and pragmatic perspective on both documentaries, focusing on the audiovisual discourse strategies they employ to reach the same implicit conclusion by different means: to suggest (without saying so explicitly and even seeking a certain balance) that the independence project in Catalonia will fail and that it would not be positive for either France or the European Union if it were to succeed.